Importance of showing HBsAg and HBcAg positivity in the liver for better aetiological definition of chronic liver disease. Issue 2 (February 1987) - Cuccurullo, L; Rambaldi, M; Iaquinto, G; Ferraraccio, F; Ambrosone, L; Giardullo, N; De Vita, A
Abstract : Serum and tissue hepatitis B virus (HBV) markers were compared in 35 alcoholic and 23 non-alcoholic subjects affected by chronic liver disease. Seventeen point one per cent of alcoholic and 21.7% of non-alcoholic subjects had HBV tissue markers, but not serum markers, for this virus. It is therefore concluded that showing the presence of HBV tissue markers permits a better aetiological definition of hepatitis B surface antigen (HBsAg) negative chronic liver disease, both in alcoholic and non-alcoholic subjects.